Effectiveness of Foliar Fungicides by Timing on Foliar Diseases on Hybrid Corn - Alison Robertson (Hello World!, 2024)
Assess the effect of timing of application of fungicides on foliar disease, evaluate the yield response of hybrid corn to foliar fungicide application, and discern differences in disease control or yield response, if any, between fungicide products..